Artificial intelligence and work : transforming work, organizations and society in an age of insecurity - Steele, Laura; Bratton, John (California, United States : Sage Publications Ltd., 2025)
'Artificial Intelligence (AI) promises to transform our homes, organizations, institutions, economies, and societies - our entire lives. It is already transforming how we work. This thought-provoking new book looks at how AI technologies effect work, organizations, society, and our planet. AI offers opportunities to free workers from mundane and dangerous tasks, facilitate new business models and boost GDP, but it is also accompanied by fears of widespread technological unemployment, as well as the erosion of agency, dignity, and human rights. It combines critical management and leadership studies, organizational sociology to the examine the central issue - the deep imbroglio of AI, corporate capital, democracy, and power. It examines how AI intersects with global megatrends, considering climate change, complex global supply chains and rising inequality'--
Keywords: Artificial intelligence -- Economic aspects; Organizational change -- Technological innovations